PENGARUH MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASI DAN KETERIKATAN KERJA YANG DIMEDIASI OLEH KEPUASAN KERJA PADA PEGAWAI DINAS PERHUBUNGAN KOTA BANDA ACEH - Mustakim Mustakim; Yurnalis Yurnalis (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This research aimed to analyze the effect of work motivation on organizational commitment and work engagement directly and indirectly through job satisfaction. The sampling technique used was cluster sampling with the size of respondents as many 119 employees, while the data analysis technique used was path analysis. The results showed that work motivation has a significant effect on job satisfaction; job satisfaction has a significant effect on organizational commitment and work engagement; work motivation has a significant effect on organizational commitment and work engagement either directly or indirectly through job satisfaction. In this study, job satisfaction acts as a partial mediation between the effect of work motivation on organizational commitment and work engagement.